Kryzys migracyjny 2015 roku w Europie i sytuacja uchodźców w czasie pandemii – czy kryzys skończył się na dobre i jaki wpływ na migrantów ma epidemia wirusa COVID-19? - Kolbusz, Paweł (Katedra Doktryn Politycznych i Prawnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
In this article author presents the migration crisis of the year 2015 and the circumstances in which the crisis took place. Having analyzed the most important reasons and events of the crisis author proves the impact of the COVID-19 pandemic on the situation of the migrants. The article also tries to answer whether the crisis is over or it is still there, only its characteristics has changed. The European perspective does not help in the recognition and interpretation of the happenings of the year 2015 in Europe. Author explains why the perspective is wrong and draws more accurate picture of the crisis in order to help better understand the crisis.
Keywords: kryzys migracyjny; uchodźcy; imigranci